Communication Dialectics of Street Musicians in Ungaran, Semarang District - Widjajantie, Kusrina; Muhammad Jazuli; Djuli Djati Prambudi (Jurnal Seni Musik, 2024)
Street  music has become a widespread social phenomenon in almost every major city worlwide, including Indonesia. Street musicians often belong to marginalized group amidst urban growth in Indonesia, particularly in Ungaran City, Semarang Regency. These musicians occupy public spaces such as intersections, traffic lights, public transport, cafes, and restaurants scattered throughout the city. This research employed qualitative method with musical ethnography approach to gain a comprehesive understanding of the communication dialectics among street musicians in public spaces. It aimed to analyze data related to the communication dialectics among street musicians occuring at traffic lights in Ungaran, including verbal, non-verbal, and musical communication. The findings are expected to provide insight into the communication dynamics during street musicians’ performances in public spaces, particularly at traffic lights, and to offer new perspectives for policymakers on maximizing public space utilization for the benefit of residents..